Labour market effects of social programmes: evidence from Ethiopia’s productive safety net - Schinaia, G (2016)
This thesis assesses how a large safety-net programme in rural Ethiopia affects local labour markets. Combining repeated cross-sections of the National Labour Force Survey with information on the geographical targeting of the programme, a differencein- differences approach is used to estimate whether employment outcomes have changed differently over time in targeted districts relative to those that did not receive the programme. The results suggest that a combination of public works employment and unconditional transfers to food-insecure households does not affect the local labour supply in this rural economy. I explore whether differential trends and population composition could explain these results, which are more likely due to programme design. Albeit scantily observed, the wages of private sector labourers also seem unaffected, in contrast to findings from similar studies focusing on labour markets from other developing countries outside Africa.